IOFI guidelines for the isolation of flavouring substances by simultaneous distillation‐extraction. (January 2015) - Cachet, T.; Brevard, H.; Cantergiani, E.; Chaintreau, A.; Demyttenaere, J.; French, L.; Gassenmeier, K.; Joulain, D.; Koenig, T.; Leijs, H.; Liddle, P.; Loesing, G.; et al.
ABSTRACT Simultaneous distillation‐extraction (SDE) combines, in a single step, hydro‐distillation of volatiles from a sample with continuous solvent extraction of the solutes dissolved in the aqueous distillate. The solvent extract containing the isolated flavour volatiles can be subsequently analysed by gas chromatography. The technique is applicable to compounds possessing a wide range of volatility, but it is suitable neither for compounds of low volatility (e.g. vanillin), nor for highly volatile materials (e.g. methanethiol). The present guidelines concern the isolation of flavouring substances by simultaneous distillation‐extraction (SDE), based on the experience of the authors in laboratories of the flavour industry. Copyright © 2014 John Wiley & Sons, Ltd.